The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1021/acssuschemeng.3c00616
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Microbial 2,3-Butanediol Production from Brewer’s Spent Grain Modeled on Pinch Technology

Abstract: Microbial production of 2,3-butanediol (BDO) has received considerable attention as a promising alternate to fossilderived BDO. In our previous work, BDO concentration >100 g/L was accumulated using brewer's spent grain (BSG) via microbial routes which was followed by techno-economic analysis of the bioprocess. In the present work, a life cycle assessment (LCA) was conducted for BDO production from the fermentation of BSG to identify the associated environmental impacts. The LCA was based on an industrial-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
(105 reference statements)
1
3
0
Order By: Relevance
“…5 shows hot spots associated with the use of water with an average contribution of about 34%, the use of urea with an input of about 29% and emissions from the use of pesticides and fertilizers of about 33%. These results are in agreement with those obtained by Tagne et al [ 9 ] and Tiwari et al [ 14 ], with low variability.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…5 shows hot spots associated with the use of water with an average contribution of about 34%, the use of urea with an input of about 29% and emissions from the use of pesticides and fertilizers of about 33%. These results are in agreement with those obtained by Tagne et al [ 9 ] and Tiwari et al [ 14 ], with low variability.…”
Section: Resultssupporting
confidence: 94%
“…González-García et al (2012), reported a net GWP of −0.619 kg CO 2 equivalent per kg ethanol [ 33 ]. In 2023, Tiwari et al [ 14 ] reported a Global Warming Potential of 7.2/kg BDO including biogenic carbon emissions. The higher Global Warming Potential in our study compared to results reported in the literature could be the result of taking into account cocoa cultivation subsystems and ethanol production up to the biorefinery stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LCA methodology has been utilized for similar studies evaluating the potential environmental impacts associated with industrial chemical production and comparing the different production approaches based on their level of impacts. Mostly all the sectors are covered: fossil-based industry, , biobased fuels and chemicals, pharmaceuticals, and the synthesis of new catalytic system from earth-abundant metals. Studies presented above, along with several others, established the suitability of the LCA methodology for pinpointing areas where different approaches to the production of chemical compounds excel in terms of environmental performance and the possible areas where process improvement efforts should be concentrated to drive significant environmental gains.…”
Section: Methodsmentioning
confidence: 99%